Impact of smartphone on mental health among medical undergraduates: A cross-sectional study - K Prafull; Aditi Rao; Vinayak Doijad; Parag Patil; Vandana S. Daulatabad; Nitin Ashok John (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Smartphones have become an indispensable part of almost everyone's life. India has now become the leading and second-largest Smartphone market in the world. It has been noted that the purpose of Smartphone usage has exceptionally changed over the past few years, especially among students, professionals, and the common man. Smartphones have now become essential and the need of the hour, and medical students are no exception. Smartphones can make "smart students smarter"! There are now 10,275 unique applications labeled under the "Medical" and "Healthcare and Fitness" categories. The common medical applications used are MedCalc, Drug Infusion, Flashcards, Encyclopedia, Merck Manual, Medscape, PubMed, Epocrates, MedlinePlus, Lab test applications, Medical Dictionary, Eponyms etc. Despite the advantages and needs of smartphones, they have proven to be a source of potential hazard to human health, not only physical but also mental, social, and emotional well-being. There is consistent evidence for co-morbidity (such as obesity, heart diseases, neck and back pain, etc.) between excessive smartphone use and other psychiatric disorders, such as depression, anxiety, obsessive and compulsive disorder (OCD), and attention deficit hyperactivity disorder (ADHD) similar to internet addiction. The significant association of this addiction with poorer sleep quality and higher perceived stress has been a cause for concern. Hence, further investigation to explore the association between smartphone addiction and mental health, this study was undertaken. MATERIALS AND METHODS: Our study was undertaken in Dr VMGMC, Solapur, from June to August 2022, after obtaining approval from the ethical committee, approval number 172/22. Total voluntary participation for the study was 600 (from first to final year), and accordingly convenient sample size was taken. RESULTS: We found that out of the total participants, 42% of the participants had an average screen time of 4-6 h daily. A very small percentage of participants (4%) spent less than two hours in front of a screen. Alarmingly, 65% of the participants had an average screen time of more than 4 hours, which puts them at risk for the negative health impacts of prolonged screen time. Around 12% of them had symptoms of mild stress, 10.3% for mild anxiety, and 15.6% for mild depression. 10.6% had symptoms of moderate stress, 23.3% for moderate anxiety, and 16% for moderate depression. A small proportion of undergraduates, that is, 5%, 16%, and 11.6%, had symptoms of severe and extremely severe stress, anxiety, and depression, respectively. CONCLUSION: The study participants did not feel a lot of stress, anxiety, or depression symptoms when smartphones were used judiciously and mostly for non-social purposes (such as studying, listening to music, or watching videos). This investigation led us to the conclusion that there are some positive effects of smartphones on mental health. However, those who spent an excessive amount of time on their smartphones for social contact, with an average screen time of 5 h, showed signs of mild to moderate sadness, moderate anxiety, and tension, demonstrating that social media had a negative impact on the mental health of medical undergraduates. Therefore, efforts should be made to inform medical students about how using a smartphone is harming their mental health.